H19 Promotes Osteoblastic Transition by Acting as ceRNA of miR-140-5p in Vascular Smooth Muscle Cells - Xu, Feng; Zhong, Jia-Yu; Guo, Bei; Lin, Xiao; Wu, Feng; Li, Fu-Xing-Zi; Shan, Su-Kang; Zheng, Ming-Hui; Wang, Yi; Xu, Qiu-Shuang; Lei, Li-Min; Tan, Chang-Ming; et al. (Frontiers in Cell and Developmental Biology, 2022)
Arterial medial calcification is a common disease in patients with type 2 diabetes, end-stage renal disease and hypertension, resulting in high incidence and mortality of cardiovascular event. H19 has been demonstrated to be involved in cardiovascular diseases like aortic valve diseases. However, role of H19 in arterial medial calcification remains largely unknown. We identified that H19 was upregulated in β-glycerophosphate (β-GP) induced vascular smooth muscle cells (VSMCs), a cellular calcification model in vitro. Overexpression of H19 potentiated while knockdown of H19 inhibited osteogenic differentiation of VSMCs, as demonstrated by changes of osteogenic genes Runx2 and ALP as well as ALP activity. Notably, H19 interacted with miR-140-5p directly, as demonstrated by luciferase report system and RIP analysis. Mechanistically, miR-140-5p attenuated osteoblastic differentiation of VSMCs by targeting Satb2 and overexpression of miR-140-5p blocked H19 induced elevation of Satb2 as well as the promotion of osteoblastic differentiation of VSMCs. Interestingly, over-expression of Satb2 induced phosphorylation of ERK1/2 and p38MAPK. In conclusion, H19 promotes VSMC calcification by acting as competing endogenous RNA of miR-140-5p and at least partially by activating Satb2-induced ERK1/2 and p38MAPK signaling.